An advanced 3D lymphatic system for assaying human cutaneous lymphangiogenesis in a microfluidic platform - Minseop Kim; Sieun Choi; Dong-Hee Choi; Jinchul Ahn; Dain Lee; Euijeong Song; Hyun Soo Kim; Mijin Kim; Sowoong Choi; Soojung Oh; Minsuh Kim; Seok Chung; et al. (NPG Asia Materials)
Abstract The human cutaneous lymphatic system strictly controls lymphatic functions by coordinating with skin cells. The lymphatic system plays important roles in removing cell waste, residual proteins, various antigens, and immune cells from tissues to maintain homeostasis and activate the immune system through the drainage of interstitial fluid1,2. The skin protects our body from external stimuli such as pathogens through the cutaneous lymphatic system3,4. Herein, to develop an in vitro human cutaneous lymphatic model, we present two 3D microfluidic platforms: a lymphangiogenesis model with a precollecting lymphatic vessel-like structure and an advanced lymphangiogenesis model with a functional cutaneous barrier and a precollecting lymphatic vessel-like structure. In addition, we rapidly analyzed prolymphangiogenic effects using methods that incorporate a high-speed image processing system and a deep learning-based vascular network analysis algorithm by 12 indices. Using these platforms, we evaluated the pro-lymphangiogenic effect of Lymphanax, a natural product derived from fresh ginseng. As a result, we demonstrated that Lymphanax induces robust lymphangiogenesis without any structural abnormalities. In conclusion, we suggest that these innovative platforms are useful for studying the interaction between the skin and lymphatic system as well as evaluating the prolymphangiogenic effects of drugs and cosmetics.